Asset building for communities and youth - Fouch, Jessica (Kansas State University, 2011)
This report reviews asset building for communities to promote youth healthy development. It addresses a comprehensive approach to youth development by engaging all members and sectors of a community. Bellevue, Washington is a community nationally recognized for its collective approach to tackling issues faced by their youth. The Search Institute’s 40 Developmental Assets 1997 Survey showed Bellevue youth possessed less than 50% of the developmental assets necessary to become responsible adults. Since receiving these results, Bellevue has continued working to improve the lives of youth in their community by utilizing the knowledge and resources of community members, organizations, and institutions. For this report, Bellevue’s collective engagement was analyzed to identify which developmental assets youth could obtain through participation, support, and engagement in various community sectors. Bellevue was used as a case study for an asset building community for youth, to determine what makes a great community for youth to live and thrive.
Keywords: community youth development; Urban Planning (0999)